Survey Investigasi Desain (SID) Air Minum di Desa Amdasa Kecamatan Wertamrian Kabupaten Maluku Tenggara - Molle, Tissa Rufus Apolos; Frans, Pieter Lourens; Toreh, Octovianus Antonius (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Limited infrastructure, hydrogeological conditions, and minimal water resources that can be processed are the main factors that affect the availability of clean water in this area. This study aims to conduct a Design Investigation Survey (SID) to explore the potential of water resources, analyze the community's drinking water needs, and design a water supply system that is appropriate to local conditions. The methods used in this study include field surveys, hydrogeological analysis, and interviews with local communities to understand water consumption patterns and the obstacles faced in obtaining clean water. The data obtained were then analyzed to determine potential water sources, supply capacity, and efficient and sustainable distribution systems. The results of the study show that the people of Amdasa Village still depend on natural water sources such as shallow wells and rainwater, which often experience a decrease in quantity and quality, especially during the dry season. From the analysis carried out, several alternative water sources were found that can be utilized by optimizing the supply system, including the use of drilled wells and gravity-based distribution systems. In addition, good water supply system planning needs to consider technical, social, and economic aspects so that it can be implemented effectively by the community.